Bee venom acupuncture for rheumatoid arthritis: a systematic review of randomised clinical trials. Issue 11 (7th November 2014) - Lee, Ju Ah; Son, Mi Ju; Choi, Jiae; Jun, Ji Hee; Kim, Jong-In; Lee, Myeong Soo
Abstract : Objective: To assess the clinical evidence for bee venom acupuncture (BVA) for rheumatoid arthritis (RA). Design: Systematic review of randomised controlled trials (RCTs). Setting: We searched 14 databases up to March 2014 without a language restriction. Participants: Patients with RA. Intervention: BVA involved injecting purified, diluted BV into acupoints. We included trials on BVA used alone or in combination with a conventional therapy versus the conventional therapy alone. Primary outcomes: Morning stiffness, pain and joint swelling Secondary outcomes: Erythrocyte sedimentation rate (ESR), C reactive protein (CRP), rheumatoid factor, the number of joints affected by RA and adverse effects likely related to RA. Results: A total of 304 potentially relevant studies were identified; only one RCT met our inclusion criteria. Compared with placebo, BVA may more effectively improve joint pain, swollen joint counts, tender joint counts, ESR and CRP but was not shown to improve morning stiffness. Conclusions: There is low-quality evidence, based on one trial, that BVA can significantly reduce pain, morning stiffness, tender joint counts, swollen joint counts and improve the quality of life of patients with RA compared with placebo (normal saline injection) control. However, the number of trials, their quality and the total sample size were too low to draw firm conclusions. Trial registration number: PROSPERO 2013: CRD42013005853.